Agama dan Politik: Konstelasi Pemikiran antara Kelompok Kultural dan Struktural pada Kalangan Kiai Pesantren di Madura - Abd Hannan; Zainuddin Syarif (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2020)
In many social science studies, Madurese people are not only known for having traditionalist religious culture, they are also known for their heterogeneous religious typologies. This study specifically examines the constellation of religious thought between the two contemporary Islamism movements in Madura, namely the Madura Ulama Alliance (AUMA) and Gesper. Both AUMA and Gesper both were born from pesantren circles, and were driven directly by the religious elite of pesantran, Kiai and lora (read: Gus in Java) pesantren. Based on the composition of its management, Gesper consists of elite boarding schools, both Kiai and lora, the majority of which are active in managing large organizations, Nahdhatul Ulama (NU). On the other hand, AUMA is mostly inhabited by Nahdhatul Ulama (NU) non-structural elites, but culturally has emotional ties with NU traditions. Therefore, although both were born and developed from a pesantren environment, in some cases AUMA and Gesper have differences, especially in terms of thinking. The condition is at the same time an explanation of why AUMA and Gesper are often involved in the struggle of religious thought in the dynamics and diversity discourse in Madura. One of them is the debate about the correct use of the term Nusantara Islam, and the latest is the dispute about whether or not to elect and appoint leaders from non-Muslims.